Finite Element Analysis of Residual Stress in Ti-6Al-4V Alloy Plate Induced by Deep Rolling Process under Complex Roller Path. (23rd December 2014) - Liou, J. J.; El-Wardany, T. I.
Abstract : The kinematics of the deep rolling tool, contact stress, and induced residual stress in the near-surface material of a flat Ti-6Al-4V alloy plate are numerically investigated. The deep rolling tool is under multiaxis nonlinear motion in the process. Unlike available deep rolling simulations in the open literature, the roller motion investigated in this study includes penetrative and slightly translational motions. A three-dimensional finite element model with dynamic explicit technique is developed to simulate the instantaneous complex roller motions during the deep rolling process. The initial motion of the rollers followed by the penetration motion to apply the load and perform the deep rolling process, the load releasing, and material recovery steps is sequentially simulated. This model is able to capture the transient characteristics of the kinematics on the roller and contacts between the roller and the plate due to variations of roller motion. The predictions show that the magnitude of roller reaction force in the penetration direction starts to decrease with time when the roller motion changes to the deep rolling step and the residual stress distributions in the near-surface material after the material recovery step varies considerably along the roller path.